Lessons learned by adapting and implementing LUCHA: a deep-structure culturally tailored healthy eating randomized pilot intervention for ethnic-diverse Latinos - Mattei, Josiemer; Caballero-González, Areli; Maafs-Rodríguez, Ana; Zhang, Amelia; O’Neill, H. June; Gago, Cristina (Frontiers in Public Health, 2024)
Objectives To report the adaptation and implementation of LUCHA (Latinos United for a Culturally Healthy Alimentation), a pilot intervention to improve dietary quality and behaviors (primary outcomes) of Latinos in Massachusetts, US, and the lessons learned during the process, including disruptions during the COVID-19 pandemic, to help shape future programs. Methods The cultural adaptation process was pre-planned using a framework, grounded in the Theory of Reasoned Action/Planned Behavior, and informed by formative mixed-methods research. A projected 75 self-identifying Latino adults (25–65y) were recruited with community-wide strategies and randomized to receive, in parallel, daily healthy eating text messages for 2 months, reinforced for 2 subsequent months, to either control (i.e., surface-level messages based on USDA MyPlate in Spanish), or intervention (i.e., deep-structure messages). The intervention messages were ethnically tailored to Caribbean or non-Caribbean heritages specifically, grounded in entrenched cultural attitudes, norms, and preferences. Trained research assistants administered questionnaires and clinical measurements at baseline, 2-months, and 4-months, in person (pre-pandemic) or via online video calls (at-pandemic). Clinicaltrials.gov registration #NCT04724382. Results LUCHA faced challenges and opportunities that conveyed lessons for future cultural adaptation and implementation of healthy eating programs. Recommendations are provided to improve digital programs for diverse ethnicities, such as widening language capabilities in texting services, using familiar video call applications, and instructing participants to measure their own clinical metrics at home using guided standardized protocols. Conclusion Tailoring nutrition programs with deep-structure cultural messages is essential when promoting healthy eating in diverse Latino heritages. LUCHA can inform programs for similar ethnic groups.